Effect of Synthesis on Quality, Electronic Properties and Environmental Stability of Individual Monolayer Ti3C2 MXene Flakes. (2nd November 2016) - Lipatov, Alexey; Alhabeb, Mohamed; Lukatskaya, Maria R.; Boson, Alex; Gogotsi, Yury; Sinitskii, Alexander
Abstract : 2D transition metal carbide Ti3 C2 Tx (T stands for surface termination), the most widely studied MXene, has shown outstanding electrochemical properties and promise for a number of bulk applications. However, electronic properties of individual MXene flakes, which are important for understanding the potential of these materials, remain largely unexplored. Herein, a modified synthetic method is reported for producing high‐quality monolayer Ti3 C2 Tx flakes. Field‐effect transistors (FETs) based on monolayer Ti3 C2 Tx flakes are fabricated and their electronic properties are measured. Individual Ti3 C2 Tx flakes exhibit a high conductivity of 4600 ± 1100 S cm −1 and field‐effect electron mobility of 2.6 ± 0.7 cm 2 V −1 s −1 . The resistivity of multilayer Ti3 C2 Tx films is only one order of magnitude higher than the resistivity of individual flakes, which indicates a surprisingly good electron transport through the surface terminations of different flakes, unlike in many other 2D materials. Finally, the fabricated FETs are used to investigate the environmental stability and kinetics of oxidation of Ti3 C2 Tx flakes in humid air. The high‐quality Ti3 C2 Tx flakes are reasonably stable and remain highly conductive even after their exposure to air for more than 24 h. It is demonstrated that after the initial exponential decay the conductivity of Ti3 C2 Tx flakes linearly decreases with time, which is consistent with their edge oxidation. Abstract : A synthetic method for high‐quality monolayer flakes of Ti3 C2 Tx, the most studied MXene material, and the investigation of their electrical properties, environmental stability, and kinetics of oxidation in air are reported. Individual monolayer Ti3 C2 Tx flakes have electrical conductivity of 4600 ± 1100 S cm −1, field‐effect electron mobility of 2.6 ± 0.7 cm 2 V −1 s −1, and remain highly conductive even after exposure to air for more than 24 h.